E-cigarette puff topography instruction to enhance switching among COPD patients who smoke - Leavens, Eleanor L. S.; Wagener, Theodore L.; Lambart, Leah; Mayo, Matthew S.; Brown, Lexie; Ellerbeck, Edward F.; Billinger, Sandra A.; Comfort, Branden; Woodward, Jennifer; Sear, Brent; Beaman, Spencer; Cox, Lisa Sanderson; et al. (Frontiers in Public Health, 2025)
IntroductionPatients suffering from chronic obstructive pulmonary disease (COPD) who smoke often face significant challenges when attempting to quit. However, switching to less harmful alternatives such as electronic cigarettes (e-cigarettes) may help mitigate tobacco-related health outcomes. Training COPD patients who smoke to adjust their puffing topography could enhance nicotine delivery and satisfaction, thereby facilitating their transition to less harmful alternatives. This pilot study examined a novel puffing topography feedback intervention to facilitate switching to e-cigarettes among COPD patients.MethodsThe study participants (N = 46) completed a 12-week e-cigarette switching trial in which they were randomized (1, 1:1) to (1) brief advice, (2) low-intensity, or (3) high-intensity topography training. This approach differed in the extent to which participants took longer puffs to maximize nicotine delivery, alleviate craving and withdrawal symptoms, and facilitate switching. Lab-based vaping sessions were conducted at weeks 0 (visits 1 and 2; separated by 48 h) and 12 (visit 3) to assess changes in puff duration (primary outcome), craving, withdrawal symptoms, and nicotine delivery. Effect size estimates are presented.ResultsPuff duration was similar across conditions at baseline (range: 1.14–1.70s), and contrary to the hypotheses, neither low- nor high-intensity training led to meaningful changes in puff duration over time compared to brief advice (Hedge’s g = 0.34). While the effects were minimal, the brief advice condition demonstrated the highest rate of complete switching (38.5%) and the largest reduction in cigarette smoking (M∆ = −17.6, SD = 10.0; Hedge’s g = 0.78) across treatment groups.DiscussionE-cigarettes exhibit high potential to minimize harm in COPD patients who smoke. However, puff topography training did not alter switch success or reduction in cigarette smoking as compared to the brief advice to switch.Clinical trial registrationNCT05510154 https://clinicaltrials.gov/study/NCT05510154.